Multiletramentos e o ensino de língua portuguesa para surdos por meio de tecnologias digitais - Gomes-Sousa, Francisco Ebson (Universidade Federal Rural do Semi-Árido, 2018)
The present research focuses on the learning of Portuguese Language (LP) by the deaf through digital technologies. In this way, the objective is to analyze how deaf students can be aided by digital technologies, especially with the use of whatsapp application, in the production of texts in LP, seeing possible teaching strategies that can be used. We specifically aim to identify the possible teaching strategies that can be used for textual production in LP by deaf students using digital technologies. We are based on the theories of Multilevel Pedagogy proposed by the New London Group (1996) and Rojo (2012) and the Deaf education in Quadros (2006). The research was quantitative and shows both descriptive and exploratory, in which a pedagogical workshop was carried out and a follow-up was carried out through social networking applications with the deaf students participating. The research universe involved a public school in the city of Mossoró - RN that specifically attends the education of the deaf, comprising 20 deaf students as subjects of this research. Thus, the corpus consists of the answers of the questionnaires on some aspects of their learning and more intensely of the interactions within the whatsapp application after the realization of the workshop. As results, we realized that the students were able to demonstrate a better textual production in LP, while we showed that the application is quite effective, mainly to foster the grammatical basis of the LP's syntactic structuring and the amplification of vocabulary of this language by deaf students, because they do not have access to the oral modality, have great difficulties in understanding the writing system and the syntactic organization of L2. Here we focus, especially from a multimodal perspective, understanding that the imaginary semiotic mode has a great influence on this teaching-learning process, since writing on digital platforms, such as whatsapp, facilitates the merge of distinct, easily accessible semiotic modes to the deaf. Therefore, a multileading perspective on the teaching of the deaf was taken into account, considering the cultural reality of deaf students and realizing that they need to become critical users of these tools that can be transformed into resources with defined teaching strategies as they are seen possibilities to be thought with the use of digital technologies in the education of the deaf.
Monografia
Keywords: Multiletramentos; Educação de Surdos; Língua Portuguesa; Tecnologias Digitais; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS